Does vitamin D supplementation in infancy reduce the risk of pre-eclampsia? - Hypponen, E; Hartikainen, AL; Sovio, U; Jarvelin, MR; Pouta, A (NATURE PUBLISHING GROUP, 2007)
Vitamin D has been suggested to affect the balance between T helper (Th1) and (Th2) type cytokines by favouring Th2 domination. We investigated the association between infant vitamin D supplementation and later pre-eclampsia, a disorder suggested to be dominated by Th1 response. We used data on 2969 women born in the Northern Finland Birth Cohort 1966 of whom 68 (2.3%) had pre-eclampsia in their first pregnancy. Risk of pre-eclampsia was halved (OR 0.49, 95% confidence interval (CI) 0.26-0.92) in participants who had received vitamin D supplementation regularly during the first year of life and this association was not affected by adjustment for own birth order, birth weight, gestational age, social class in 1966 and hospitalizations or pregnancy-induced hypertension of their mothers. Together with earlier observations on a reduced risk of type 1 diabetes after vitamin D supplementation, these data suggest that vitamin D intake in infancy may affect long-term programming of the immune response pattern.